Effects of Sodium Ferulate on Cardiac Hypertrophy Are via the CaSR-Mediated Signaling Pathway - Chen, Panpan; Wen, Zhaoqin; Shi, Wanlan; Li, Zhongli; Chen, Xiaoyan; Gao, Yang; Xu, Shangfu; Gong, Qihai; Deng, Jiang (Frontiers in Pharmacology, 2021)
As a common complication of many cardiovascular diseases, cardiac hypertrophy is characterized by increased cardiac cell volume, reorganization of the cytoskeleton, and the reactivation of fetal genes such as cardiac natriuretic peptide and β-myosin heavy chain. Cardiac hypertrophy is a distinguishing feature of some cardiovascular diseases. Our previous study showed that sodium ferulate (SF) alleviates myocardial hypertrophy induced by coarctation of the abdominal aorta, and these protective effects may be related to the inhibition of protein kinase C (PKC) and mitogen-activated protein kinase (MAPK) signaling pathways. This study investigated the inhibitory effect and mechanism of SF on myocardial hypertrophy in spontaneously hypertensive rats (SHRs). The effects of SF on cardiac hypertrophy were evaluated using echocardiographic measurement, pathological analysis, and detection of atrial natriuretic peptide (ANP) and β-myosin heavy chain (β-MHC) expression. To investigate the mechanisms underlying the anti-hypertrophic effects of SF, the calcium-sensing receptor (CaSR), calcineurin (CaN), nuclear factor of activated T cells 3 (NFAT3), zinc finger transcription factor (GATA4), protein kinase C beta (PKC-β), Raf-1, extracellular signal-regulated kinase 1/2 (ERK 1/2), and mitogen-activated protein kinase phosphatase-1 (MKP-1) were detected by molecular biology techniques. Treatment with SF ameliorated myocardial hypertrophy in 26-week-old SHRs. In addition, it downregulated the levels of ANP, β-MHC, CaSR, CaN, NFAT3, phosphorylated GATA4 (p-GATA4), PKC-β, Raf-1, and p-ERK 1/2; and upregulated the levels of p-NFAT3 and MKP-1. These results suggest that the effects of SF on cardiac hypertrophy are related to regulation of the CaSR-mediated signaling pathway.